Синтез та встановлення будови нового класу лігандів фосфорильованих арилсульфоніламідів - Скопенко, В.В.; Мороз, О.В.; Труш, В.О.; Труш, Є.А.; Амірханов, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
A series of potential chelate agents of the sulfonylamide type with the general formula RSO2NHPO(R1)2, where R = −C6H5, R1 = −OCH3 (HL¹), −OCH2C6H5 (HL²), −OC6H4CH3−p (HL³), −O(CH2)2OCH3 (HL^4), −N(CH3)C6H5 (HL^5), −N(CH3)CH2C6H5 (HL^6), and their sodium salts are synthesized and characterized by IR- and ¹H, ³¹P NMR-spectroscopies. For the ligands HL¹ and HL³, the dimeric and polymeric structures are established using the X-ray diffraction analysis.